The culture of boredom - Ros Velasco, Josefa, 1987- (Critical studies (Amsterdam, Netherlands), 2020)
"The Culture of Boredom was born in fall 2017, when the outstanding national and international specialists in Boredom Studies, from a variety of disciplines such as psychology, philosophy, sociology, anthropology, comparative literature, and aesthetics, to name a few, and including myself, started discussing the importance of research and work together to move forward the study of boredom as a modern phenomenon, traditionally approached by sociologists and philosophers, by involving new discourses on modern boredom from literature and art as well as from sociology and philosophy, in order to throw light on the holistic comprehension of boredom beyond psychology"--